2004
DOI: 10.1063/1.1667495
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Cluster data on chorus emissions using the backward wave oscillator model

Abstract: The measurements of chorus emissions by four closely separated Cluster spacecraft provide important information concerning the chorus generation mechanism. They confirm such properties of the wave source as their strong localization near the equatorial cross section of a magnetic flux tube, an almost parallel average wave-vector direction with respect to the geomagnetic field, and an energy flux direction pointing outward from the generation region. Inside this region, Cluster discovered strong temporal and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
126
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(154 citation statements)
references
References 22 publications
25
126
3
Order By: Relevance
“…A linear theory of the magnetospheric BWO considered in [7,10] allows one to find the threshold flux of energetic electrons and the instability growth rate for a given excess over the threshold. Qualitative consideration of the nonlinear stage of the instability [8] and comparison with statistical properties of chorus emissions detected onboard the satellite Magion 5 [3] and with the Cluster spacecraft data, obtained in the generation region [11], showed that the BWO model can explain both the typical amplitude and frequency drift of chorus elements.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A linear theory of the magnetospheric BWO considered in [7,10] allows one to find the threshold flux of energetic electrons and the instability growth rate for a given excess over the threshold. Qualitative consideration of the nonlinear stage of the instability [8] and comparison with statistical properties of chorus emissions detected onboard the satellite Magion 5 [3] and with the Cluster spacecraft data, obtained in the generation region [11], showed that the BWO model can explain both the typical amplitude and frequency drift of chorus elements.…”
Section: Introductionmentioning
confidence: 94%
“…As for the specific features of the chorus-spectrum formation, a closed self-consistent scenario of this process has been proposed fairly recently [7][8][9][10][11]. This model is based on the following experimentally established properties of chorus emissions:…”
Section: Introductionmentioning
confidence: 99%
“…Properties of the observed chorus emissions are compared by Trakhtengerts et al (2004) with the theoretical properties of the BWO mechanism. According to this theory, a succession of whistler wave packets is generated in a nearequatorial source region with temporal and spatial characteristics close to those observed by the four CLUSTER spacecraft.…”
Section: Comparison Of Observations With Nonlinear Theorymentioning
confidence: 99%
“…Chorus typically has a discrete structure of separate wave packets (elements) in a frequency range from a few hundreds of Hz to several kHz (see reviews by Omura et al, 1991;Sazhin and Hayakawa, 1992, and references therein). Trakhtengerts et al (2007) showed that the spectrum of chorus wave packets lacks lower frequencies close to the center of the source region and explained this effect on the basis of the backward wave oscillator model (Trakhtengerts, 1995(Trakhtengerts, , 1999Trakhtengerts and Rycroft, 2000;Trakhtengerts et al, 2004). This model links the frequency of chorus wave packets to the parallel component of the velocity of a steplike deformation of the electron distribution function.…”
Section: Introductionmentioning
confidence: 99%